Европейская цивилизация глазами тюрко-мусульман Российской империи XIX в. (по страницам романа И.Гаспринского «Френкистан мектюплери») - Богданович, И.А.; Ганкевич, В.Ю. (Материалы по археологии, истории и этнографии Таврии, 2002)
Важным общественным вопросом, волновавшим мусульманскую интеллигенцию XIX в., было отношение к европейской научно-технической цивилизации. Они были вынуждены признать, что азиатский аграрный Восток существенно отставал от европейского индустриального Запада. In this article the author traces back as the Muslim intellectuals of the end of the 19th century considered the achievements of European civilization on the basis of the novel “French Letters” by I. Gasprinsky. In the first part of the novel the main character- a Muslim scrutinizes the state of enlightenment, science and technology in Europe, state system of education in France, style of life of European peoples, judicial system and the status of hospitals and prisons, the position of women in the society. The author came to the conclusion that in spite of all the achievements in European civilization it lacks “the core of justice”, that is why it could not be used as a progressive model for imitation for the Muslims. In the second chapter of the novel I. Gasprinsky described a fantastic Muslim country, where scientific and technical achievements were used and the high level of Muslim ethics and code of morals were observed.